Formal analysis of efficiency and safety in IPSec based on internet key exchange protocol. (1st January 2015) - Ahmim, Marwa; Babes, Malika; Ghoualmi-Zine, Nacira
IPSec is a framework of open standards for providing secure communications over internet protocol (IP) networks. The kernel of the IP security architecture is the internet key exchange protocol (IKE). IKE is an automatic method for key exchange and confidential parameters used in AH and ESP encapsulation. However, IKE protocol has a number of weaknesses; the two most important ones are the high complexity of the protocol and the vulnerability to passive and active attacks. To deal with these problems, several improvements have been proposed. In this paper, we propose a new IKE protocol based on elliptic curve cryptography, which aims to achieve a high-security level and efficiency. The security analysis and formal verification using automated validation of internet security protocols and applications (AVISPA) tools show that our contribution can resist to various attack types such as modification, reflection, replay, DoS and man-in-the-middle. The comparison between our proposed IKE protocol and other IKE protocols shows that our new protocol is more efficient with less computation complexity.